An Assessment of Flow-Mediated Dilatation in Behçet’s Disease - Ruken YÜKSEKKAYA; Fatih ÇELİKYAY and Fatih KOÇ and Çağlar DENİZ and Erkan GÖKÇE and Mehmet Murat FIRAT and Jale YÜKSEK3 (Archives of Rheumatology, 2012)
Objectives: This study aims to evaluate the early development of atherosclerosis in patients with Behçet’s disease (BD) using flow-mediated dilatation (FMD) method under Doppler ultrasonography (US). Patients and methods: Thirty patients with BD and 25 healthy volunteers were included. Doppler US was used to measure the basal and post-reactive hyperemic diameters, peak systolic velocities, resistivity indices, and blood flow volumes of the brachial arteries. Flowmediated dilatation was defined as the percentage of difference between the post-reactive hyperemic and basal diameters. Results: The mean FMD value of the BD group (10.8±12.7%) was significantly lower compared to the control group (26±18.6%). No statistically significant difference in other parameters was found between the groups. Conclusion: Flow-mediated dilatation under Doppler US is simple and effective non-invasive method for predicting the early development of atherosclerosis in patients with BD.